Mild versus severe COVID-19: Laboratory markers - Velavan, Thirumalaisamy P.; Meyer, Christian G. (International journal of infectious diseases, 2020)
•Several laboratory parameters may facilitate the assessment of COVID-19 severity•Discriminating mild from severe COVID-19 disease•Cumulative data from clinical characteristics of COVID-19 patients•Low lymphocyte count as well as the serum levels of CRP, D-dimers, ferritin and IL-6 The number of COVID-19 patients is dramatically increasing worldwide. Treatment in intensive care units (ICU) has become a major challenge; therefore, early recognition of severe forms is absolutely essential for timely triaging of patients. While the clinical status, in particular peripheral oxygen saturation (SpO2) levels, and concurrent comorbidities of COVID-19 patients largely determine the need for their admittance to ICUs, several laboratory parameters may facilitate the assessment of disease severity. Clinicians should consider low lymphocyte count as well as the serum levels of CRP, D-dimers, ferritin, cardiac troponin and IL-6, which may be used in risk stratification to predict severe and fatal COVID-19 in hospitalised patients. It is more likely that the course of the disease will be unfavourable if some or all of these parameters are altered.